Testes de germinação e vigor em sementes de feijão irrigado cultivar BRS Pérola - MARCONDES, Bruno Ruan Rossatti,; LOPES, Adriano da Silva,; FRANCO, Jhonatan da Silva,; Marcos Jefferson, (ANAIS DO ENIC, 2024)
-